Quality of Sorghum Silage Fermented with Starch of Gebanga Flour(Corypha gebanga) and Lactic Acid Bacteria as Additives - Lado, Lilo J. M. Christna Kale; Utomo, Ristianto; Noviandi, Cuk Tri; Ngadiyono, Nono (Faculty of Animal Science, Universitas Gadjah Mada, ISSTAP 2017, 2017)
The carbohydrate-rich feed was commonly used as an additive in ensiling process. However, there has been lack of scientific reports on the usage of starch of gebanga (Corypha gebanga) flour as additive combined with lactic acid bacteria (LAB). The objective of this study was to determine the quality of sorghum silage treated with the starch of gebanga flour and LAB as additives. Twenty units of mini silos (5 treatments × 4 replicates) were examined for chemical characteristics of sorghum silage after 21 d of ensiling period where every four mini silos contain sorghum without additives (control), and with either the starch of gebanga flour at a level of 4% (G4), 4% + 0.1% LAB (G4LAB), 8% (G8), or 8% + 0.1% LAB (G8LAB) of total dry matter of silage. Results of the study showed that the quality of sorghum silage were influenced by gebanga flour additive with or without Lactobacillus plantarum (P<0.05). Inclusion of 8% gebanga flour with or without LAB increased dry and organic matters of the silage. All treatments resulted in acidic condition and lower the pH of silage. The greatest lactic acid concentration was recorded for G8 (6.01 g/kg). In summary, the inclusion of the gebanga flour and Lactobacillus plantarum as additives improved the quality of sorghum silage.